Economic value of biodiversity conservation perceived by local visitors in FRIM Selangor Forest Park - Abdullah, Mukrimah (2017)
Biodiversity is the variability among living organism from all sources includes terrestrial, marine, and other ecosystems and the ecological complexes of which they are parts. Conservation of biodiversity is one of the efforts to ensure sustainability of biodiversity which often under-valued and ignored especially in decision making process. One of the principles of Malaysia’s NPBD (1998) stated that biodiversity is a national heritage and it must be sustainably managed and wisely utilized today and conserved for future generation. In order to manage and conserve biodiversity, information about the economic value of biodiversity conservation must be obtained. Environmental valuation technique can provide useful evidence to support such policies by quantifying the economic value associated with the protection of biological resources. This valuation will give the monetary value to FRIM’s biodiversity and will make a contribution in order to obtain the status as a world heritage site by UNESCO, expected to achieve in 2019/2020. Therefore, this study was conducted to estimate the economic value of biodiversity conservation at FRIM Selangor Forest Park (FRIM). FRIM offers a variety of forest ecosystem services such as biodiversity conservation, recreation, ecotourism and nature-environmental education. The data for this study was obtained by using face-to-face interview with guided questionnaire and survey toolkits. A total of 433 respondents were successfully interview in four month from September to December 2014, where most of them are the first time visitors. This study employed the Choice Modelling (CM) and Contingent Valuation Method (CVM) approaches to estimates the economic value of conserving biodiversity and to evaluate their preferences towards the biodiversity conservation attributes. For CM, a hypothetical scenario was created by combining four attributes (excluding price) at few different levels. Information on the level for each attributes can be from any related sources such as annual reports, and expertise judgement. In this study, the selected attributes were wildlife protection, carbon sequestration, recreation and nature education where, each attributes may consist of one to three levels depending on the attributes. The level can be the improvement from the current condition, or to the other management options. In this study, baseline information for levels was taken from FRIM’s Annual Report, Books published by FRIM, and data published by FRIM’s researchers. The CM findings showed that visitors are willing to pay for an improvement from the status quo to better levels. The variable WLIFE2, CARBON2, CARBON3 and RECR3 were statistically significant at one percent level while RECR2, EDU2 and EDU3 were statistically significant at five percent level. Price has negative sign which is in line with the theoretical expectation; this indicates that as the conservation fee increases, respondents are less likely to contribute because of the decrease in the utility level. The CM results found that on average, the marginal values are between RM3.11 to RM9.44 per entrance for the presence of the attributes (carbon, wildlife protection, recreation and education) and all attributes are highly favored compared to the status quo (baseline) and statistically significant below five percent. This finding shows visitor were willing to pay for the improvement at minimum RM3.11 and maximum at RM9.44 per entrance for conserving biodiversity specifically at FRIM which could contribute extra revenue between RM 1.4 million to RM 4.2 million annually (by taking into account 455,014 visitors on average visitors from 2007 to 2016). For CVM results, frequency analysis shows the level of willingness to pay (WTP) for biodiversity conservation fund was between RM1.00 to RM30.00 per entrance with the mean WTP of RM5.67 per entrance. The Pearson Correlation analysis shows that the respondents’ maximum willingness-to-pay and the bid price posted is significant at 1% level. Few variables were included into three models and found that the highest estimated mean WTP was RM8.12 per entrance compared to another two models with WTP for logistic and OLS are RM7.90 and RM5.70. The yearly calculated conservation value or benefits of FRIM’s biodiversity conservation based on the highest mean willingness to pay computed for the year 2007 until 2016 ranged from RM 1.5 million to RM 8.1 million with average of RM 3.5 million. Estimated benefits of conserving biodiversity for the past 10 years increase almost 228% or 2.2 times in year 2016. If there is a proposal to charge (e.g. in the form of tax) to contribute to biodiversity conservation fund, the amount found in this study was RM8.12 per entrance. This value can be used by the authorities to determine the fees conservation / appropriate conservation. It is noted that visitors were only willing to pay for the improvement of biodiversity attributes and its conservation only. That means the conservation fee collected must be used for the conservation of biodiversity at FRIM only. The results suggested from the visitor’s interest to contribute in conserving biodiversity at FRIM, it also indicates that more concerted effort is needed by management to conserve and protect FRIM. The findings of this study provides useful evidence to support and helps the formulation of policies that protect biodiversity by quantifying the economic value associated with the protection of biological resources; help the management or stakeholders (government or private sectors) to improve in sustainable forest management and assist the conservation of biodiversity for the benefits of present and future generations and lastly contribute in realizing FRIM’s aspiration to become a World Heritage site by United Nations Educational, Scientific and Cultural Organization (UNESCO) by 2019/2020.